Calcite mesocrystals : a very effective block polyelectrolyte for crystal "Morphing" - Wang, Tongxin; Verch, Andreas; Börner, Hans G.; Cölfen, Helmut; Antonietti, Markus (My University, 2009)
A family of calcite nanocrystal superstructures with unusual morphology were obtained from crystallization of calcite by the CO2 gas diffusion technique in the presence of a bioinspired double hydrophilic block copolymer, polyethyleneglycol-block-poly (L-aspartic acid). From the typical calcite rhombohedra as a starting situation, the morphology can be systematically varied via various unusual porous mesocrystal morphologies to hemispheres composed of fine calcite triangles. The formation of mesocrystals is starting at a polymer concentration of only 10-3 g/L and shows two remarkable results: (a) the reported bio-inspired block copolymer is the so far most active polymer for mesocrystal formation reported to our knowledge, and (b) the data prove that nucleation promoters exist, which can form nanocrystals for mesocrystal formation even without enhanced colloidal stabilization. This gives mesocrystal formation a much broader operation range than previously assumed.
Keywords: 540